Primary curriculum design & delivery - Frater, Glynis (London Corwin, 2023)
This is a practical guide for school leaders and teachers who have responsibility for designing and delivering a sequenced, knowledge-rich and skills-focused primary curriculum. It considers the elements that underpin a high-quality curriculum and how to create a sequential learning experience for pupils across the primary phase. It explores a range of practical tools and techniques that can support staff to build a cohesive curriculum where pupils build on their learning from year to year with high-quality outcomes for all learners, whatever their starting point. -- Provided by publisher.
Chapter 1: The Curriculum as the fulcrum for learning and achievement - a review of the past 10 years -- Chapter 2: Curriculum Intent, Implementation and Impact - Creating a whole school synergy -- Chapter 3: Creating a high-quality curriculum as a tapestry of learning: skills, concepts and knowledge -- Chapter 4: Skills for learning: weaving literacy, numeracy and thinking skills across the curriculum -- Chapter 5: Concepts and Subject Knowledge: creating subject specific and cross-curricular connections -- Chapter 6: Sequencing the learning for depth and progression -- Chapter 7: Assessing learning: creating a collaborative and cohesive strategy for positive formative assessment -- Chapter 8 - Curriculum Cohesion - a school in synergy -- Chapter 9: Drawing together the strands that define a high quality curriculum
Includes bibliographical references and index.
Keywords: Curriculum planning; Education, Elementary -- Curricula